Performance of cashew (Anacardium occidentale) varieties under different planting density for growth and yield traits - Nayak, M G; Muralidhara, B M; Janani, P; Savadi, Siddanna (The Indian Journal of Agricultural Sciences, 2020)
Cashew (Anacardium occidentale L) is an important tropical tree crop revered for its economic and nutritional needs. The demand for cashew is increasing significantly in both domestic and international markets. Planting density and tree canopy influence the yield performances of tree crops. Planting of trees at higher densities in orchards offers high yield potential. In the current study, a field experiment was conducted to study the effect of planting density on growth and yield of different varieties of cashew during 2013-14 to 2017-18. The three varieties, viz. H-130, NRCC Sel. 2 and Bhaskara were planted at three different planting systems, viz. ultra density (2.5 × 2.5 m), high density (5.0 × 5.0 m) and normal density (7.5 × 7.5 m) and evaluated for growth and yield traits. The heading back was carried out in ultra density planting during the last week of May in all the years. The results revealed significant differences for yield and related traits among cashew varieties under different plant densities. The maximum yield was recorded in variety H-130 planted at 2.5 × 2.5 m spacing during second year (1248 kg/ha), third year (2234 kg/ha) and fourth (2432 kg/ha) year of planting and minimum (154 kg/ha) was observed in variety Bhaskara at 2.5 × 2.5 m spacing. The variety H-130 performed well in all the three different planting systems compare to NRCC Sel. 2 and Bhaskara due to positive response of pruning.